Production and functional analysis of rat CD59 and chimeric CD59‐Crry as active soluble proteins in Pichia pastoris - Quigg, R J (Blackwell Science Inc, 2000)
Crry (CR1‐related gene/protein) is a rodent complement regulator that inhibits C3 convertases. CD59 is a conserved protein inhibitor active towards C8 and C9. We have previously produced rat Crry as a recombinant soluble (rs) protein in Pichia pastoris. In this study we produced functionally active rat rsCD59 and a chimeric rsCD59‐Crry protein in P. pastoris. The GPI anchor addition site of rat CD59 (Asn‐79) was replaced either by a stop codon to produce rsCD59, or with the sequence of the first five short consensus repeats of Crry to produce rsCD59‐Crry. Proteins were generated by fermentation and purified by affinity chromatography on an anti‐CD59 column. In a standard classical pathway haemolysis assay, all three rs proteins had inhibitory activity, with 50% inhibition at 0·5 µm (rsCrry and rsCD59‐Crry) and 4·4 µm (rsCD59). In an assay examining inhibition of C5b‐9, in which C5b‐7 was first formed, followed by purified C8 and C9, rsCD59 and rsCD59‐Crry were active with 50% inhibition at 0·8 µm (rsCD59‐Crry) and 1·3 µm (rsCD59). The degree of inhibition was independent of whether the C8 and C9 were of rat or human origin. Therefore, we have produced rsCD59 and rsCD59‐Crry in P. pastoris. The rsCD59 retains its inhibitory activity towards C5b‐9, while rsCD59‐Crry appears to have the combined activities of Crry and CD59. In a haemolytic assay, the inclusion of CD59 to Crry is of no additional benefit to Crry, which may illustrate the overall importance of the C3 convertase step. Yet, inclusion of Crry to CD59 increases the potency of CD59 towards C5b‐9.